Dukungan Angkatan Muda Siliwangi Terhadap Pasangan Ridwan Kamil - Uu pada Pilgub Jabar Tahun 2018 - Kurnia Kurnia; Muradi Muradi; Widya Setiabudi Sumadinata (Mahesa Research Center, 2021)
Angkatan Muda Siliwangi (AMS) as a community organization participated in politics in the 2018 West Java Governor and Vice Governor elections, throught its support for Ridwan Kamil and Uu Ruzhanul Ulum. This research is about analysis related to thr mobilization of votes out by the AMS to capture voter’s votes. This research used qualitative methods with descriptive analysis techniques. Data collection wa carried out thought in depth interviews with related parties and document studies. The analysis of this researh was carried out by means of reduction, presentayion, conclusions and verification. The results showed that AMS was participated tu supporting Ridwan Kamil and Uu Ruzhanul Ulum in election. The member of AMS has done any activity, including: participation in volunteer formation; active in the Ridwan Kamil and Uu Ruzhanul Ulum’s campaign; socializing and communication with the society as the voter, including leaders and senior, to other millenials. In the other side, Ridwan Kamil and Uu Ruzhanul Ulum’s campaign is carried out through social media.